An Introduction to Chemoinformatics - Andrew R Leach (Springer ( India ) Pvt. Ltd., 2007)
"This text aims to provide a comprehensive introduction to the major techniques of chemoinformatics. The first part of the book deals with the representation of 2D and 3D molecular structures, the calculation of molecular descriptors and the construction of mathematical models. The second part describes other important topics including molecular similarity and diversity, the analysis of large data sets, virtual